Integrated use of chemical and liquid biofertilizers for improved seed and oil yields in rapeseed (Brassica napus) in north-western Himalayas - PRAJAPATI, VED; MANKOTIA, B S; MANUJA, SANDEEP (The Indian Journal of Agricultural Sciences, 2025)
A present study was carried out during winter (rabi) season 2021–22 and 2022–23 at Shivalik Agricultural Research and Extension Centre, Chaudhary Sarwan Kumar Himachal Pradesh Krishi Vishwavidalaya, Kangra, Himachal Pradesh to investigate the influence of fertility levels along with seed inoculations with liquid biofertilizers on seed yield, quality parameter and soil microbial population after harvest of rapeseed (Brassica napus L.) variety ‘GSC-7’. The research was carried out using split plot design (SPD) with three fertility levels, viz. Control; 75% of recommended dose of fertilizer (RDF) and 100% RDF (120-60-40 kg NPK/ha) in main-plots in addition to six treatments of liquid biofertilizers, viz. Azotobacter; phosphate solubilizing microorganisms (PSMO); potassium mobilizing biofertilizer (KMB); NPK consortia + zinc solubilizing biofertilizer (ZSB); ZSB and control (no biofertilizer) as sub-plots, replicated thrice. The pooled data analysis of two-year recorded significantly higher values on number of primary and secondary branches/plant, siliquae/plant, seeds/siliqua, seed yield (1.89 t/ha), oil content (41.7%), oil yield of 792.2 kg/ha and soil microbial population in 100% RDF treatment followed by 75% RDF and control. The findings demonstrated that seed inoculation with Azotobacter and PSMO were found to be the most efficient biofertilizers. Azotobacter recorded significantly higher yield attributing characteristics and seed yield (1.68 t/ha), oil content (41.5%) and oil yield (718.1 kg/ha) along with higher soil microbial population after harvest of crop.